Civil engineering procedure (ICE Publishing, 2020)
'Civil Engineering Procedure' is an indispensable guide which describes and explains the stages of work for a project from the first consideration through to completion of construction and then beyond to handing over the resulting structures and services for use. Updates to this edition include new case studies in each chapter, coverage of NEC4 and other civil engineering conditions of contract, recent initiatives to improve project and programme delivery including advances in digital construction and modern methods of construction. This edition also includes reflective questions at the end of each chapter which have been designed to assist students and professional review candidates.